In vivo and in vitro evidence that intrinsic upper‐ and lower‐limb skeletal muscle function is unaffected by ageing and disuse in oldest‐old humans. (28th May 2015) - Venturelli, M.; Saggin, P.; Muti, E.; Naro, F.; Cancellara, L.; Toniolo, L.; Tarperi, C.; Calabria, E.; Richardson, R. S.; Reggiani, C.; Schena, F.
Abstract Aim To parse out the impact of advanced ageing and disuse on skeletal muscle function, we utilized both in vivo and in vitro techniques to comprehensively assess upper‐ and lower‐limb muscle contractile properties in 8 young (YG; 25 ± 6 years) and 8 oldest‐old mobile (OM; 87 ± 5 years) and 8 immobile (OI; 88 ± 4 years) women. Methods In vivo, maximal voluntary contraction (MVC), electrically evoked resting twitch force (RT), and physiological cross‐sectional area (PCSA) of the quadriceps and elbow flexors were assessed. Muscle biopsies of the vastus lateralis and biceps brachii facilitated the in vitro assessment of single fibre‐specific tension (Po). Results In vivo, compared to the young, both the OM and OI exhibited a more pronounced loss of MVC in the lower limb [OM (−60%) and OI (−75%)] than the upper limb (OM = −51%; OI = −47%). Taking into account the reduction in muscle PCSA (OM = −10%; OI = −18%), only evident in the lower limb, by calculating voluntary muscle‐specific force, the lower limb of the OI (−40%) was more compromised than the OM (−13%). However, in vivo, RT in both upper and lower limbs (approx. 9.8 N m cm−2) and Po (approx. 123 mN mm−2), assessed in vitro, implies preserved intrinsic contractile function in all muscles of the oldest‐old and were well correlated (r = 0.81). Conclusion These findings suggest that in the oldest‐old, neither advanced ageing nor disuse, per se, impacts intrinsic skeletal muscle function, as assessed in vitro. However, in vivo, muscle function is attenuated by age and exacerbated by disuse, implicating factors other than skeletal muscle, such as neuromuscular control, in this diminution of function.